2018
DOI: 10.1177/1534735418795301
|View full text |Cite
|
Sign up to set email alerts
|

Group Yoga Effects on Cancer Patient and Caregiver Symptom Distress: Assessment of Self-reported Symptoms at a Comprehensive Cancer Center

Abstract: Background. Complementary and integrative health approaches such as yoga provide support for psychosocial health. We explored the effects of group-based yoga classes offered through an integrative medicine center at a comprehensive cancer center. Methods. Patients and caregivers had access to two yoga group classes: a lower intensity (YLow) or higher intensity (YHigh) class. Participants completed the Edmonton Symptom Assessment System (ESAS; scale 0-10, 10 most severe) immediately before and after the class. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…With regard to the impact on anxiety, a recent meta-analysis supported the usefulness of yoga or meditation as a complementary or solo treatment of anxiety or depression [ 33 ]. It was previously found that a 12-month yoga program or an 8-week meditation programs could reduce anxiety and depression and diminish physical and psychological distress [ 17 , 18 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the impact on anxiety, a recent meta-analysis supported the usefulness of yoga or meditation as a complementary or solo treatment of anxiety or depression [ 33 ]. It was previously found that a 12-month yoga program or an 8-week meditation programs could reduce anxiety and depression and diminish physical and psychological distress [ 17 , 18 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in HRV is linked to adaptive emotional regulation strategies [ 15 , 16 ]. Practices that focus on the interactions among brain, body, mind, and behavior, such as yoga, are reported to improve the well-being and cardiac balance in informal caregivers [ 17 , 18 ]. “Meditation” is another ancient approach to the cultivation of well-being [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the impact on anxiety, a recent meta-analysis supported the usefulness of yoga or meditation as a complementary or solo treatment of anxiety or depression [28]. It has previously been found that a 12-month yoga programs or an 8-week meditation programs can reduce anxiety and depression and diminish physical and psychological distress [15,14,29].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in HRV has been linked to adaptive emotional regulation strategies [12,13]. Practices that focus on the interactions among brain, body, mind, and behavior, such as yoga, have been reported to improve well-being and cardiac balance in informal caregivers [14,15]. "Meditation" is another ancient approach to the cultivation of well-being [16].…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa penulis menggambarkan peningkatan pengaruh positif dan penurunan pengaruh negatif pada pasien dengan kanker yang berpartisipasi dalam program yoga (Siedentopf et al, 2013). Penelitian sebelumnya menemukan manfaat yoga pada pasien kanker yaitu meningkatkan kesehatan, kualitas hidup dan fisik, mengurangi kecemasan, depresi, gangguan tidur, kelelahan, tekanan psikososial dan gejala muskuloskeletal (Lopez et al, 2018).…”
Section: )unclassified